Natural occurrence of aflatoxins in dry fruits and edible nuts. (September 2015) - Masood, Muhammad; Iqbal, Shahzad Zafar; Asi, Muhammad Rafique; Malik, Noeen
Abstract: A total 307 samples of dry fruits and edible nuts from Northern areas and Khyber Pakhtunkhwa, Pakistan were evaluated for the presence of aflatoxins (AFs). The samples were analysed using a reversed phase HPLC, equipped with fluorescence detector. Results have revealed that 132 out of 307 samples of dry fruits and nuts were found positive with aflatoxin B1 (AFB1 ) and total AFs. The highest mean level of total AFs i.e. 7.89 ± 0.99 μg/kg was found in peanuts without shell and lowest mean level (2.45 ± 0.11 μg/kg) was found in watermelon seeds without shell samples. Samples 75 (24%) were found contaminated with AFB1, ranged from 8 to 10 μg/kg and 41 (13%) samples were found above the level of 10 μg/kg for total AFs. The high occurrence of AFs may cause health hazards for consumers and limit exports. Highlights: The study was focused to investigate the occurrence and levels of AFs in dry fruits and nuts. Samples 132/307 were found positive with aflatoxins contamination. Total 24 and 13% samples were found above the permissible limits for AFB1 and total AFs, respectively. The contamination of aflatoxins in dry fruits and nuts may pose health hazards.